THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE MINDS OF YOUNG PEOPLE - Berdiqulova M. E; Toshboyeva B. J (TADQIQOTLAR, 2026)
Annotation This article analyzes the role of rapidly developing digital technologies, particularly artificial intelligence, in modern human life. It focuses on the impact of excessive use of the Internet and digital gadgets on young people’s thinking abilities, learning motivation, and psychological activity. The advantages and disadvantages of using artificial intelligence in the education system are discussed based on foreign experiences. In addition, the article examines the competition between artificial intelligence and human intelligence, as well as its influence on the labor market. The study emphasizes the importance of maintaininga balance between technological development and natural intelligence, highlighting the need for conscious and purposeful use of digital technologies to ensure intellectual growth and professional development in the digital era.